Finding the Comfort Zone: Bacteria-Surface Interaction in Microbial Fuel Cells - Frühauf-Wyllie, Hanna Marianne; Justus Liebig University Giessen (My University, 2022)
In microbial fuel cells (MFC) (biological) waste can be converted to electrical power and thus contribute to the development of a sustainable circular economy. The core of any MFC are exoelectric bacteria that oxidise organic substrates and transfer resulting electrons to an electrode as terminal electron acceptor. Exoelectric bacteria that rely on direct electron transfer require immediate contact with the electrode, which gives the physico-chemical properties of the electrode surface particular importance. This is the case for the MFC model organism Geobacter sulfurreducens that was used in this work. The aim was to improve bacteria-surface interaction by adapting the electrode surface characteristics in order to increase MFC efficiency. The bacterial adhesion to a surface depends on a variety of physico-chemical factors; the one in focus for this work was surface charge. Layer-by-layer coating with differently charged polyelectrolytes was used to modify the surface charge of MFC anodes. Subsequently, the effect on selected MFC performance indicators was assessed. MFC with indium tin oxide (ITO) anodes (polarisation +0.1 V vs. Standard Hydrogen Electrode) were used to define reference values against which the results on coated anodes could be compared. Anode surface charge influenced all analysed performance indicators and the results were subject to a general correlation: The thicker and more viable the biofilm, the higher were current density and coulombic efficiency, and the shorter was the start-up phase. However, none of the coatings significantly improved the performance compared to the non-coated electrodes (maximum current density on ITO: 399 μAcm-2 ± 24% (n = 3), maximum current density with negatively charged polystyrene sulfonate as terminating layer: 456 and 377 μAcm-2, respectively). The other coatings resulted in poorer performance. This contradicted the hypothesis accepted in literature that a positive surface charge is generally beneficial for bacterial adhesion. To gain a better understanding of the initial phase of biofilm formation, an electrochemical flow cell that can be operated under a confocal laser scanning microscope was used. The initially desired application of the flow cell (in vivo biofilm analysis) failed due to a fluorescent G. sulfurreducens strain that a) did not form a G. sulfurreducens-typical biofilm and b) did not develop sufficient fluorescence for microscopic analysis under anaerobic conditions. However, the results emphasised that the optimisation of MFC is difficult due to the high number of factors that influence the performance. The interaction between electrode surface coating, pH and salinity of the medium and any surface-active macromolecules released by bacteria will add on to the sole effect of the surface modification and complicates the isolated analysis of influencing factors. Also, the comparison to existing MFC improvements through surface modification is made difficult by the multivariate system the MFC is. Nevertheless, monitoring of the initial bacteria-surface interaction in vivo and recording the corresponding current response is a promising strategy when aiming to improve MFC anode material and can hopefully push this promising technology another step ahead.
Keywords: Microbial Fuel Cells; Biofilm; Electroactive bacteria; Geobacter sulfurreducens; CLSM; Electrode surface charge; ddc:570